Basic Needs and Absolute Poverty in Lithuania: Method and Estimation - Navickė, Jekaterina; Čižauskaitė, Aušra; Užgalė, Ugnė (Lithuanian Journal of Statistics, 2019)
We propose a methodology for estimating the cost of the basic needs and applying it on the data for Lithuania in a decade after the EU accession (2006-2016). The basic food costs account for the minimal nutrition requirements, while the cost of other needs is estimated in relative terms, taking actual consumption patterns in the population into account. A reduction in the cost of the basic needs for additional members of the household is accounted for by a specially constructed consumption-based equivalence scale estimated on the HBS data. We show that the cost of the basic needs in Lithuania is close to the relative at-risk-of-poverty line (at 60% of the median equivalized disposable income) for a single adult but exceeds it for larger households. The share of people with income below the basic needs’ cost was above the relative at-risk-of-poverty levels in the EU-SILC data for all years, except of 2016. Albeit, the actual level might be lower due to the under-reporting of shadow income in the EU-SILC. Ability to meet basic needs and related absolute poverty indicators shows anti-cyclical dynamics in times of the economic growth and recession. Children are consistently the most deprived group of the Lithuanian population when it comes to meeting the basic needs. The official absolute poverty indicator used in Lithuania under-estimates the cost of the basic needs for households with more than one member.
Keywords: basic needs; absolute poverty; Lithuania; equivalence scale; HBS; SILC